Educational program on nurses attitude toward documentation in Al-Furat Alawsatt teaching hospital - Jebur, Hayder Ghaleb; Mohameed, Shatha Saadi (International journal of health sciences, 2022)
Nursing documentation’s purpose is to show that an organization maintains thorough written record of its planning, delivery, assessment, and evaluation of patient care, as well as to serve as a source of information for new nurses and maybe for nursing theory development.It contains all written information related to the patient’s condition and needs.From September 21, 2020 to March 7, 2022, the researcher at Al-Furat Al-Awsat Teaching Hospital in Al-Najaf City used a quasi-experimental design with two groups and two evaluation stages to assess the effectiveness of the educational program in improving attitudes, and practices related to nursing documentation. A total of (50) nurses were randomly assigned to two groups and enrolled using non-probability deliberate selection procedures. To the control group,which maintained the same level of attitudes, and practices with a modest decline in nursing documentation attitudes, and practices. Furthermore, the education program was shown to be effective in increasing nurses’ documentation attitudes, and behaviors, according to the study. Furthermore, a method like this is useful in shielding nurses from being documented.Based on the above-mentioned findings, the current study suggest that the Ministry of Health should consider nurses’ benefits.